The Effectiveness of Implementing Agroforestry Systems in Improving Soil Quality - Bidadari, Sabti Gina; Fauzi, M. Taufik; Sudharmawan, A. A. (Jurnal Biologi Tropis, 2025)
Intensive annual farming practices can damage soil structure, reduce soil organic matter content, and cause soil erosion. This condition results in decreased soil fertility, which in turn affects agricultural productivity. Collective efforts are needed to adopt environmentally friendly agricultural practices to improve soil quality. The purpose of this article is to determine the effectiveness of implementing agroforestry systems in improving soil quality. The method used in this writing is a literature study conducted by collecting data from various sources such as scientific journals, books, seminar proceedings, and so on. This literature review found that increasing tree diversity in complex agroforestry systems significantly increased soil organic carbon in the soil layer. Compared to bare land, agroforestry systems showed significant increases in soil organic carbon and accessible nutrients. Improving soil health and ecosystem function requires microbial diversity, biological activity, and the production and preservation of soil organic carbon, all of which are facilitated by agroforestry systems. Agroforestry systems, which combine food crops with tree crops, offer ecological services such as increasing fertility, reducing erosion, and improving the physical, chemical, and biological quality of the soil. The conclusion is that agroforestry systems are effective in improving soil quality.